Implementable Factors for Sustainable Agricultural Policy in Metro City - Arbiyansah Krisnantoro; Retno Widodo Dwi Pramono (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Conservation of agricultural land for food sovereignty is one of the SDGs' agenda. In Indonesia, this objective is stated in the Sustainable Food Agricultural Land (LP2B) policy outlined in Law No. 41/2009, which followed by regulations below to the level of the Regional Regulation. In the Metro City, this is stated in Regional Regulation No. 21/2016 to be the basis for a policy of protection of 1,567.5 hectares of paddy fields. This regulation aims to support food sovereignty and maintain the ecological balance of the environment. The problem arises because the paddy fields designated by LP2B are private land so that not all owners are willing to implement this policy. This study aims to analyze the factors that affect the level of willingness of landowners with a quantitative approach by analyzing land data with multiple linear regression analysis techniques. A sample of 513 parcels was taken from the Farmers Owning Farmers population of 6,060 HHs based on Agricultural Survey data, BPS Lampung 2018. In general, from the results of the analysis, the highest coefficient on object characteristics was variable land productivity while the characteristics of subjects were multifunctional knowledge of paddy fields.